THE INFLUENCE OF BRAND REPUTATION, PRODUCT QUALITY, AND PRICE ON REPURCHASE INTENTION OF RESPIRO RIDINGWARE PRODUCTS IN SURABAYA - Dinda alkarimah, Dinda; Megasari, Aisyah Darti; Zaman, Komarun; Nuryadi (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to analyze the extent to which Brand Reputation, Product Quality, and Price influence consumers' Repurchase Intention of Respiro Ridingware products in Surabaya. This research uses a quantitative approach. The sampling technique applied is probability sampling with a simple random sampling method, and the Slovin formula was used to determine the number of respondents, totaling 100 participants. The research findings indicate that Brand Reputation, Product Quality, and Price simultaneously have a significant influence on consumers' Repurchase Intention.Keywords: Brand Reputation, Product Quality, Price and Repurchase Intention.